Project scheduling for swallow nest construction using the critical path method - Asrul, Muhamad Rizki; Angelita Tindaon, Merry Christina; Azzahra, Dita Nabila; Wulandari, Rani; Ismayanti, Rika (Enrichment : Journal of Management, 2025)
Indonesia is a major producer of swallow nests with high export value, but constructing swallow houses remains challenging due to biological and technical complexities. This study aimed to develop a more efficient construction schedule using the Critical Path Method (CPM). CPM was chosen to identify activity paths that directly influenced project duration, thereby minimizing delay risks. A quantitative approach was used through a case study of a four-storey swallow house project in Batua Village, Kutai Kartanegara. Data were collected via observation, interviews, and technical documentation, and analyzed using Microsoft Project to determine critical paths and estimated durations. The analysis revealed that out of 42 activities, several were on the critical path with zero slack. By focusing on these critical activities, the project duration was reduced from the original 220 calendar days to 184 days. This demonstrated that CPM effectively increased scheduling efficiency by aligning with both the biological and technical requirements of swallow nest construction. The findings provided valuable insights for swallow house developers to implement more structured and efficient planning, while also encouraging integration between civil and ecological engineering in specialized construction practices